Biological activity validation of a computationally designed Rituximab/CD3 T cell engager targeting CD20+ cancers with multiple mechanisms of action. (22nd October 2021) - Cai, Wenyan; Dong, Jianbo; Gallolu Kankanamalage, Sachith; Titong, Allison; Shi, Jiadong; Jia, Zhejun; Wang, Bo; Huang, Cai; Zhang, Jing; Lin, Jun; Kan, Steven Z; Han, Shuhua; et al.
Abstract: Background: Bispecific T cell engaging antibodies (TEAs) with one arm targeting a cancer antigen and another arm binding to CD3 have demonstrated impressive efficacy in multiple clinical studies. However, establishing a safety/efficacy balance remains challenging. For instance, some TEAs have severe safety issues. Additionally, not all patients or all cancer cells of one patient respond equally to TEAs. Methods: Here, we developed a next-generation bispecific TEA with better safety/efficacy balance and expanded mechanisms of action. Using the computer-aided antibody design strategy, we replaced heavy chain complementarity-determining regions (HCDRs) in one Rituximab arm with HCDRs from a CD3 antibody and generated a novel CD20/CD3 bispecific antibody. Results: After series of computer-aided sequence optimization, the lead molecule, GB261, showed great safety/efficacy balance both in vitro and in animal studies. GB261 exhibited high affinity to CD20 and ultra-low affinity to CD3. It showed comparable T cell activation and reduced cytokine secretion compared with a benchmark antibody (BM). ADCC and CDC caused by GB261 only killed CD20+ cells but not CD3+ cells. It exhibited better RRCL cell killing than the BM in a PBMC-engrafted, therapeutic treatment mouse model and good safety in cynomolgus monkeys. Conclusions: Thus, GB261 is a promising novel TEA against CD20+ cancers.